1994
DOI: 10.1080/87567555.1994.9926831
|View full text |Cite
|
Sign up to set email alerts
|

Social Accounts and Metaphors about Cheating

Abstract: ollege student cheating, or academic dishonesty, has been a topic C of much interest to education researchers. A thorough, multidisciplinary literature search on the subject reveals at least 200 journal articles and reports. The research literature on college cheating might be divided into the following categories: reporting and defining types of cheating or academic misconduct; reactions by researchers to academic cheating (How serious is the problem?); methodologies for studying academic dishonesty; causes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 32 publications
0
31
0
1
Order By: Relevance
“…In a study, Payne and Nantz (1994) affirmed that the social construction plays a strong and a vital role in nurturing the habit of plagiarism in students. They observed that the academic behavior of students is all an affair of his/her social set up.…”
Section: Environmental Influencesmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study, Payne and Nantz (1994) affirmed that the social construction plays a strong and a vital role in nurturing the habit of plagiarism in students. They observed that the academic behavior of students is all an affair of his/her social set up.…”
Section: Environmental Influencesmentioning
confidence: 97%
“…The same behavioral pattern of students was observed by Barnett & Dalton (1981). In a research, Payne & Nantz (1994) found that students see cheating during exams and cheating including other forms of academic purposes differently. In an observation study Roberts & Rabinowitz (1992) found that the overall students perceptions chiefly depends upon the interplay of multiple factors such as needs, wants, situational provocations, alluring opportunities, and intentional approach.…”
Section: Students' Attitudementioning
confidence: 99%
“…Studies by Stevens and Stevens (1987) and Payne and Nantz (1994) also support this reason for cheating. The students' perception that the risk of getting caught cheating is low also plays an important role in a student's participation in cheating behaviors (Stevens & Stevens; Payne & Nantz).…”
Section: Why Students Cheatmentioning
confidence: 81%
“…This pressure is generated by parents or the desire to succeed (Barnett & Dalton, 1981;Hilbert, 1987;Payne & Nantz, 1994;Stevens & Stevens, 1987). Students feel that they need high grades in order to successfully enter competitive programs such as medical school.…”
Section: Why Students Cheatmentioning
confidence: 99%
See 1 more Smart Citation